Conceptual and Pictorial Looking Through in Emilio Garroni’s Aesthetics - Giambrone, Giulia (Aesthetica Preprint, 2022)
With the notion of aesthetics as looking-through, Emilio Garroni encapsulates in two words the necessary condition for the existence of the work of art. In relation to the contemporary art scene, the looking-through outlined in its theoretical nuances, becomes a filter for interpreting the nature of the work, nowadays in the guise of the most varied hybrids. Two great poles – the conceptual and the pictorial – direct new artistic trends. Even if contaminated, the form of the work always appears referable to the influence of one of the two poles. By bringing Garroni’s Aesthetics into the field of the conceptual or pictorial, the work of art acquires new light. In particular, topics such as the spectator-entity and its looking-through, aesthetic experience as a possible experience, questioning and the effort of understanding, find a place in relation to the conceptual. Instead, the exemplarity of aesthetic experience, the artwork as a source of possible schemata, ‘sensefulness’ and the ‘must-make-sense’ find the same in relation to the pictorial. A new looking-through arises which renews the aesthetic experience and turns its exemplarity into a must-make-sense image. While the work changes, its demand to be looked at ‘in the middle’ remains, where the observer’s gaze becomes a part of the form. Where the possibility of the work itself lies, there also lies the viewer who questions himself, striving. Therefore, the work generates constantly new and ever-changing schemata for understanding reality, getting the original sensefulness precisely from its placement balanced between sense and non-sense.